SUN-Family Protein UvSUN1 Regulates the Development and Virulence of Ustilaginoidea virens - Yu, Mina; Yu, Junjie; Cao, Huijuan; Song, Tianqiao; Pan, Xiayan; Qi, Zhongqiang; Du, Yan; Zhang, Rongsheng; Huang, Shiwen; Liu, Wende; Liu, Yongfeng (Frontiers in Microbiology, 2021)
Ustilaginoidea virens, the causal agent of rice false smut disease, is an important plant pathogen that causes severe quantitative and qualitative losses in rice worldwide. UvSUN1 is the only member of Group-I SUN family proteins in U. virens. In this work, the role of UvSUN1 in different aspects of the U. virens biology was studied by phenotypic analysis of Uvsun1 knockout strains. We identified that UvSUN1 was expressed during both conidial germination and the infection of rice. Disruption of the Uvsun1 gene affected the hyphal growth, conidiation, morphology of hyphae and conidia, adhesion and virulence. We also found that UvSUN1 is involved in the production of toxic compounds, which are able to inhibit elongation of the germinated seeds. Moreover, RNA-seq data showed that knockout of Uvsun1 resulted in misregulation of a subset of genes involved in signal recognition and transduction system, glycometabolism, cell wall integrity, and secondary metabolism. Collectively, this study reveals that Uvsun1 is required for growth, cell wall integrity and pathogenicity of U. virens, thereby providing new insights into the function of SUN family proteins in the growth and pathogenesis of this pathogen.